Metode Case Based Reasoning Untuk Identifikasi Penyakit Tanaman Padi - Yumai Wendra; Alwendi Alwendi; Ardi Ardi; Dasril Aldo (JURSIMA (Jurnal Sistem Informasi dan Manajemen), 2020)
After wheat and maize, rice (Oryza sativa L.) is a very important food crop in the world. Rice is a rice-producing crop and is a very important food crop. Most of the world's population, especially in Asia, is still used as a staple food. During the cultivation process, many rice plants are susceptible to disease and pest attacks, including: leaf blight, tongguo grass, rice bursts, and dwarf grass. Generally, when rice plants are attacked by diseases and pests, farmers use pesticides directly or by means of countermeasures which are sometimes not suitable for diseases and pests that are infected in rice plants. As a result, prevention is not optimal and can even cause new diseases and pests. Assisting farmers in identifying early symptoms of plant diseases and rice pests, so that treatment of plant diseases and insect pests is more concentrated and maximally is the aim of this study. The processed data were 4 pests and diseases which were processed using case-based reasoning. This method will diagnose the types of rice and insect pests and its treatment steps with an accuracy of 95%. Therefore, this method is suitable for the diagnosis of rice disease.